Vers une architecture in teaching - Ortiz dos Santos, D.; Sequeira, M.; Boone, V.; Lausch, F.; Miguel, C. (LC. Revue de recherches sur Le Corbusier, 2025)
Vers une architecture in Teaching investigates how Le Corbusier’s seminal book has been interpreted, appropriated, and contested within the pedagogical context of ETH Zurich. Drawing upon archival materials, teaching documents, and testimonies from educators since the late 1950s, this research traces the oscillating presence of Vers une architecture in architectural education—from its canonical status to its critical reassessment. The study reveals how successive generations of design studio professors have mobilised Le Corbusier’s text as a tool for aesthetic reflection, ideological debate, or historical distancing, exploring broader transformations in architectural culture. By juxtaposing these pedagogical practices, the article situates ETH Zurich as a microcosm of shifting modernist legacies: a space where the authority of the modern canon is continually questioned and reinterpreted. Ultimately, Vers une architecture in Teaching reconsiders how the teaching of architecture constructs its own histories through acts of reading, criticism, and reinvention.